Does Medicaid Coverage for Pregnant Women Affect Prenatal Health Behaviors? - Dhaval M. Dave; Robert Kaestner; George Wehby (Institute for the Study of Labor (IZA), 2016)
Despite plausible mechanisms, little research has evaluated potential changes in health behaviors as a result of the Medicaid expansions of the 1980s and 1990s. In this paper, we provide the first national study of the effects of Medicaid on health behaviors for pregnant women, which is a group of particular interest given evidence of the importance of prenatal health to later life outcomes. We exploit exogenous variation from the Medicaid income eligibility expansions for pregnant women during late-1980s through mid-1990s to examine the effects of these policy changes on smoking, weight gain and other maternal health indicators. We find that the 13 percentage point increase in Medicaid eligibility during the study period was associated with approximately a 3 percent increase in smoking and a small increase in pregnancy weight gain for most of the sample. The increase in smoking, which is a significant cause of poor infant health, may partly explain why Medicaid expansions have not been associated with substantial improvement in infant health.
Keywords: D1; H0; I12; I13; I18; 330; Medicaid; insurance; moral hazard; health; smoking; weight; prenatal care; infant health